Utilization of Personal Protective Equipment in Construction Industry of Nepal - Acharya, Uddhav Raj; Shrestha, Santosh Kumar (Advances in Engineering and Technology: An International Journal, 2021)
Construction industry is one of the most dangerous industries worldwide. Use of personal protective equipment reduces injuries associated with it. This study has been undertaken to find out safety improvement measures and enforcement of statutory provisions available for safety practices, to analyze the current issues regarding application of PPE and to identify key factors preventing effective use of safety wears in construction industry of Nepal. The methodology adopted consists of comprehensive review of literature and questionnaire survey.100 sets of questionnaires to the professionals and 385 to the site operatives were administered. The collected data were analyzed using relative mean score and independent samples test and then ranked as per their significance. This study concluded that routine check of scaffold and ladder, in house safety training, daily consciousness of safety practice, etc. will improve workers’ safety practices. Wearing PPE can help protect from work related injuries, feeling responsible for wearing PPE all the times, asking supervisors for provision of appropriate and adequate PPE but the management has not maintained sufficient stock of appropriate safety wears are the current issues regarding application of PPE. Based on the result of Independent Samples T-test, safety wears are not comfortable to wear with, operatives’ engagement in improper conduct that could endanger their safety, ineffective communication between safety managers and workers are the major factors preventing effective use of safety wears.